Constituents and Biological Activity of Sudanese Tephrosia apollina (Fabaceae) Seed Oil - Karim, Mohamed Abdel; El-Faiz,F.,; Mohamed Alaa, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2019)
Tephrosia is a genus in the family Fabaceae. This genus is distributed in tropical and sub-tropical regions.Tephrosia genus manifested a range of biological activities including: antifungal, antiplasmodial, antiinflammatory, antiulcer , antidiabetic and anticancer activities. In this  study GC-MS analysis of Tephrosia apollina oil revealed the presence of the following major constituents: i)9-octadecenoic acid methyl ester(31.79%);  (ii)9,12-octadecadienoic acid methyl ester(21.34%). ;(iii) hexadecanoic acid methyl ester(17.86%) and  (iv)methyl stearate(16.07%).The oil was evaluated for antimicrobial potential. The studied oil showed significant activity against Bacillus subtilis , Staphylococcus aureus and Escherichia coli .It exhibited  moderate activity against other test organisms.